Analysing Teacher’s Difficulties in Teaching Listening Comprehension - Putri Ayu Lestari; Renny Kurniasari; Winny Agustia Riznanda (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This study aimed to investigate the teacher’s difficulties in teaching listening at MAN 1 Palembang. This study used a qualitative research. One of the qualitative research designs applied in this study was case study design. The participant of this study was one of English teachers at MAN 1 Palembang. The participant of this study was taken from one of the four English teachers at MAN 1 Palembang by using criterion sampling strategy. The data were collected through interview. The data were analyzed and presented descriptively. there are six steps commonly used in analyzing qualitative data, as follows; (1) the researcher have to be familiar with entire body of data (2) generate codes, (3) search for themes (4) review themes (5) define and name themes, and (6) produce the report. The results of this study showed that the difficulties faced by the teacher’s in teaching listening at MAN 1 Palembang were related to as follows: (a) the students' psychological factor; (b) students’ background knowledge; (c) students’ attitude; (d) lack of students’ vocabulary; (e) teaching aids or media; (f) the material; and (g) method of teaching listening comprehension.